Teknik Self-Management dalam Konseling Kelompok untuk Mengatasi Permasalahan Perilaku Siswa Sekolah Menengah - Denisa Septiani; Juwita Madira; Dea Kartika Utami; Berlian Cahyani; Ratna Sari Dewi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the effectiveness of self-management techniques in group counseling for secondary school students. The background of the research is based on the increasing behavioral problems among students, such as academic procrastination, gadget addiction, and low discipline, which hinder their academic and personal development. Self-management is considered an effective strategy to promote students’ independence in managing their behavior and emotions. The research used a library research method by analyzing relevant journals and scholarly articles published between 2017 and 2025. The findings indicate that self-management techniques in group counseling are effective in reducing negative behaviors, improving social skills, and strengthening students’ character and sense of responsibility. These results provide important implications for school counselors in designing systematic and practical services that support holistic student development.